2003
DOI: 10.1038/nature01904
|View full text |Cite
|
Sign up to set email alerts
|

A uniquely specialized ear in a very early tetrapod

Abstract: The Late Devonian genus Ichthyostega was for many decades the earliest known tetrapod, and the sole representative of a transitional form between a fish and a land vertebrate. However, despite being known since 1932 (ref. 1) from a large collection of specimens, its morphology remained enigmatic and not what was expected of a very primitive tetrapod. Its apparent specializations led it to be considered as a "blind offshoot" or "sidebranch" off the tetrapod family tree, and recent cladistic analyses have disagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 17 publications
6
75
0
2
Order By: Relevance
“…Indeed, Coates and Clack (1995) suggested that the whole Devonian tetrapod radiation including not only Acanthostega, but also Ichthyostega and the possible basal amniote Tulerpeton (Lebedev and Coates 1995) were entirely aquatic animals. Support for this idea has recently come from the discovery that Ichthyostega does in fact also possess gill bars, and has a unique ear structure designed for hearing under water rather than in air (Clack et al 2003). This view is consistent with the argument, put forward by Janis and Farmer (1999), that a primarily aquatic tetrapod would not be expected to lose its gills even if living in low-oxygen waters, because of the effectiveness of gills in nitrogen and carbon dioxide excretion.…”
Section: The Vertebrate Conquest Of Land: Origin Of the Amniotasupporting
confidence: 70%
“…Indeed, Coates and Clack (1995) suggested that the whole Devonian tetrapod radiation including not only Acanthostega, but also Ichthyostega and the possible basal amniote Tulerpeton (Lebedev and Coates 1995) were entirely aquatic animals. Support for this idea has recently come from the discovery that Ichthyostega does in fact also possess gill bars, and has a unique ear structure designed for hearing under water rather than in air (Clack et al 2003). This view is consistent with the argument, put forward by Janis and Farmer (1999), that a primarily aquatic tetrapod would not be expected to lose its gills even if living in low-oxygen waters, because of the effectiveness of gills in nitrogen and carbon dioxide excretion.…”
Section: The Vertebrate Conquest Of Land: Origin Of the Amniotasupporting
confidence: 70%
“…It is commonly accepted that the evolution of the middle ear is associated with the transition from an aquatic to a terrestrial lifestyle. However, recent work on the earliest tetrapods has shown that these animals (32) possessed a specialized ossicle in the middle ear despite their largely aquatic lifestyle (33,34). Furthermore, the tetrapod middle ear, with a tympanum, evolved independently at least four times in terrestrial tetrapods (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…With a few modifications such as the gradual withdrawal of the notochord and the rearward extension of the parasphenoid across the basicranial fissure, this new braincase morphology remained essentially constant up into the base of the tetrapod crown group 42 . Even the highly specialized braincase of Ichthyostega is recognizably derived from this pattern 4 . With regard to the postcranial skeleton, Ventastega consistently resembles Acanthostega; all the changes that distinguish Devonian tetrapod from elpistostegid limb girdles-loss of the supracleithrum and post-temporal; enlargement of the scapulocoracoid; loss of the coracoid foramen; enlargement of the interclavicle, creation of a sacrum-seem to have already occurred.…”
Section: The Postcranial Skeletonmentioning
confidence: 99%
“…A minor change in interpretation concerns a large and (in Ventastega) bi-lobed nerve foramen on the anterior face of the prootic; this was interpreted as transmitting nerve VII in Acanthostega 7 , but its large size, position on the anterior face of the otoccipital, and bilobed shape all suggest that it is actually the opening for nerve V. The presence of a fenestra vestibuli and absence of a lateral commissure suggest that the dorsal-most element of the hyoid arch was a stapes, rather than a hyomandibula as seen in Panderichthys 24,27,30 and Tiktaalik 22 . Compared to the overall similarity between Ventastega and Acanthostega, the otoccipital region of Ichthyostega is very distinctive and evidently autapomorphic 4 .…”
Section: The Skullmentioning
confidence: 99%